Involvement of Secretin in the Control of Cell Survival and Synaptic Plasticity in the Central Nervous System - Wang, Lei; Zhang, Li (Frontiers in Neuroscience, 2020)
With emerging evidence showing a wide distribution of secretin (SCT) and its receptor (SCTR) in the central nervous system (CNS), the putative neuropeptide role of SCT has become more appreciated since the disruption of SCT/SCTR axis affects various neural functions. This mini review thus focuses on the effects of SCT on cell survival and synaptic plasticity, both of which play critical roles in constructing and maintaining neural circuits with optimal output of behavioral phenotypes. Specifically, SCT-dependent cellular and molecular mechanisms that may regulate these two aspects will be discussed. The potential complementary or synergistical mechanisms between SCT and other peptides of the SCT superfamily will also be discussed for bridging their actions in the brain. A full understanding of functional SCT/SCTR in the brain may lead to future perspectives regarding therapeutic implications of SCT in relieving neural symptoms.